The importance of molecular diagnosis in controlling the old-world screwworm fly Chrysomya bezziana (Vill.) (Diptera: Calliphoriadae) using the sterile insect technique in Iraq - Shatha Ahmed Mahdi (Journal of Kerbala for Agricultural Sciences, 2026)
Larvae of the fly Chrysomya bezziana (Vill.) (Diptera: Calliphoridae), responsible for myiasis, were collected from 60 infected cattle in three Iraqi governorates (Diyala, Baghdad, and Maysan). A total of 600 adult flies were subjected to mitochondrial cytochrome b gene sequencing, targeting a 317 bp fragment of the 3' terminal region. The analysis revealed the presence of two distinct haplotypes: one occurring in Diyala and Baghdad, and the other in Maysan, southern Iraq. The two haplotypes differed in the number of nucleotide deletions and substitutions, with a total of 189 genetic mutations identified—79 in samples from Baghdad and Diyala combined, and 110 in those from Maysan. Minor differences in morphological traits, such as size and shape, were also observed. These findings indicate genetic diversity among Ch. bezziana populations across Iraq. Such diversity suggests that a single laboratory colony could be sufficient for implementing the Sterile Insect Technique (SIT) within an integrated control program.